2019
DOI: 10.1002/tesq.559
|View full text |Cite
|
Sign up to set email alerts
|

A Thematic Linguistic Analysis of TESOL Students’ Commitment to Intercultural Communication Values

Abstract: This article describes a study of TESOL preservice teacher journals that used a thematic linguistic framework of analysis aimed at revealing the extent of their commitment to intercultural communication values, as evidenced by their attitude to cultural differences and stereotyping, and their stance markers. Nearly all entries showed the students’ ability to decenter, question the values of their own culture, and accept the values of the other culture. A minority of students took a nonessentialist view of cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Cutting J used the subjective language analysis framework to analyze pre-service teachers' attitudes about intercultural communication values, and teachers were able to teach to influence students' intercultural communication skills and to discard their cultural values to some extent. This addresses the need for teachers to take the initiative in understanding students' beliefs and helping them develop correct cultural awareness in teaching intercultural communication [21]. Lou N M K A discussed the influence between incremental and entity beliefs during language learning and showed that this influence could also impact students' intercultural communicative competence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cutting J used the subjective language analysis framework to analyze pre-service teachers' attitudes about intercultural communication values, and teachers were able to teach to influence students' intercultural communication skills and to discard their cultural values to some extent. This addresses the need for teachers to take the initiative in understanding students' beliefs and helping them develop correct cultural awareness in teaching intercultural communication [21]. Lou N M K A discussed the influence between incremental and entity beliefs during language learning and showed that this influence could also impact students' intercultural communicative competence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…How should they promote cultural exchange and dissemination so as to realize effective cross-cultural communication. How can foreign language teachers in colleges and universities understand the similarities and differences in the history and culture of various countries and increase their sensitivity and adaptability to cultural differences so as to provide effective talents for cross-cultural [2][3]. Foreign language teachers in colleges and universities are organizers and guides in the classroom.…”
Section: Introductionmentioning
confidence: 99%